Multivariate analyses of cellular fatty acids in Bacteroides, Prevotella, Porphyromonas, Wolinella, and Campylobacter spp. - Brondz, I (1991)
The genera Bacteroides, Wolinella, and Campylobacter contain several similar species that require taxonomic revision. Fatty acid profiles of whole bacterial cells have proven useful for taxonomy. In this study, cellular fatty acids from Bacteroides, Prevotella, Porphyromonas, Wolinella, and Campylobacter spp. were identified and quantitated by gas chromatography and gas chromatography-mass spectrometry, and the data were subjected to principal component analyses. Bacteroides fragilis, the type species of the genus Bacteroides, was distinct from the other organisms. While Bacteroides gracilis, Wolinella succinogenes, Wolinella curva, Wolinella recta, and Campylobacter fetus subsp. venerealis were close to each other, Prevotella (Bacteroides) buccae, Prevotella oralis, Prevotella oris, Prevotella disiens, Prevotella veroralis, Prevotella heparinolyticus, Porphyromonas (Bacteroides) endodontalis, and Bacteroides ureolyticus could be distinguished. B. fragilis was characterized by the presence of C3OH-i-1-, Ca-15, and Ci-15 and the absence of C12:0 and unsaturated fatty acids. For comparison, B. gracilis, B. ureolyticus, W. succinogenes, W. curva, W. recta, and Campylobacter fetus subsp. venerealis contained C12:0, C16:1, C18:1, and C3-OH-14 acids but lacked branched hydroxy and branched nonhydroxy acids. B. gracilis and B. ureolyticus are not "true" bacteroides.